2013
DOI: 10.1159/000355305
|View full text |Cite
|
Sign up to set email alerts
|

Boosted Rat Natural Xenoantibodies Cross-React with <b><i>Enterococcus faecalis</i></b> by Targeting Melibiose and <smlcap>L</smlcap>-Rhamnose

Abstract: Natural antibodies include a subset described as xenoantibodies considered to be directed at microorganisms and also cross-react with antigens of unrelated species. In this study, we generated T-cell-independent (TI) and T-cell-dependent (TD) xenoantibodies in Lewis rats with hamster and pig blood injections. TI anti-hamster and anti-pig IgM and IgG xenoantibodies cross-reacted with Enterococcus faecalis but not with Escherichia coli isolated from the blood of Lewis rats after cecal ligation and puncture (CLP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Nonspecific effects of lipopolysaccharides on antiviral type I interferons are involved in these effects. In addition to effects mediated through cellular mechanisms, generation of natural xenoantibodies also induces nonspecific effects during infection, as shown by Perez-Cruz et al [7]. Finally, nonspecific adaptive characteristics of innate immunity are shown to occur and to be sustained for at least 1 year after vaccination in humans.…”
mentioning
confidence: 94%
“…Nonspecific effects of lipopolysaccharides on antiviral type I interferons are involved in these effects. In addition to effects mediated through cellular mechanisms, generation of natural xenoantibodies also induces nonspecific effects during infection, as shown by Perez-Cruz et al [7]. Finally, nonspecific adaptive characteristics of innate immunity are shown to occur and to be sustained for at least 1 year after vaccination in humans.…”
mentioning
confidence: 94%
“…This condition predicted later risk for enteric peritonitis in peritoneal dialysis patients and mortality in both peritoneal dialysis and hemodialysis patients [ 11 ]. In addition, we have recently shown that boosted TI xenoantibodies in rats by exposure to hamster or pig antigens cross-react to Enterococcus faecalis by targeting melibiose and L-rhamnose carbohydrates [ 12 ]. This circumstance was associated with reduced survival of these animals after CLP, which was not observed with the generation of IgG antibodies.…”
Section: Introductionmentioning
confidence: 99%